2022
DOI: 10.3389/fmed.2022.843749
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Signature Genes and Characterizations of Tumor Immune Microenvironment and Tumor Purity in Lung Adenocarcinoma Based on Machine Learning

Abstract: The implication of the Estimation of Stromal and Immune cells in Malignant tumor tissues using expression data (ESTIMATE) method to determine the tumor microenvironment (TME) and tumor immune score including tumor purity represents an efficient method to identify and assess biomarkers for immunotherapy response in precision medicine. In this study we utilized a machine learning algorithm to analyze the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus database (GEO) lung adenocarcinoma (LUAD) transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Combined with our results that GIMAP6 expression was significantly upregulated in DM, we speculated that GIMAP6 might contribute to regulating the development, activation, and apoptosis of CD4 + T cells. GIMAP6 has been recognized as a prognostic biomarker in head and neck squamous cell carcinoma, breast cancer, and female lung adenocarcinoma and as a predictor of response to immunotherapy in lung adenocarcinoma ( 64 – 66 ). We are looking forward to furthering studies exploring the relationship between GIMAP6 and CD4 + T cells in DM.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with our results that GIMAP6 expression was significantly upregulated in DM, we speculated that GIMAP6 might contribute to regulating the development, activation, and apoptosis of CD4 + T cells. GIMAP6 has been recognized as a prognostic biomarker in head and neck squamous cell carcinoma, breast cancer, and female lung adenocarcinoma and as a predictor of response to immunotherapy in lung adenocarcinoma ( 64 – 66 ). We are looking forward to furthering studies exploring the relationship between GIMAP6 and CD4 + T cells in DM.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps background levels of EPA and DHA or the response to these fatty acids will also vary within each subpopulation of subjects with diabetes. Future studies using machine-learning approaches, as demonstrated in other disciplines, in the context of experiments with EPA/DHA will assist in moving the field forward [41][42][43][44].…”
Section: Integration Of Differing Inputs Of Heterogeneity Will Requir...mentioning
confidence: 99%
“…Marker genes for 29 immune cell subtypes were obtained from published literature (Table S1). The ESTIMATE score system consists of the immune and stromal scores [12]. ESTIMATE analyzes bulk tumor data and predicts tumor purity and immune as well as stromal cell infiltrations by single-sample gene set expression analysis (ssGSEA) [10].…”
Section: Evaluation Of Immune Cells and Acquisition Of Estimate Scoresmentioning
confidence: 99%